Civil Society is a Free Democratic Legal Society Based on Spiritual and Cultural Values - Tulkin, Kuyliyev (Miasto Przyszłości, 2024)
The article states that civil society is an important factor in human social activity. This article analyzes the process of evolutionary transition in our country, modern technological changes, and reforming the system of spiritual spheres. Spirituality is a powerful factor that awakens national pride and honor in every sensible person and citizen, embodying identity, giving strength to realize the goals and dreams of the nation, and encouraging the nation to act. The article also mentioned that the reforms carried out in our republic serve the freedom of citizens and their ability to find their place in society.